IT IS NEGATIVE OR POSITIVE IMPACT OF OBESITY ON EDUCATION - Normurodova Sevinch; Safarova Shohsanam (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Obesity has notably expanded for the reason that 1980 and emerge as a international epidemic. Obesity-related health problems and the poor social and monetary implications of weight problems have led worldwide establishments and nations to fight it. This study investigates the function of instructional attainment and monetary globalization in the global incidence of weight problems in samples of adult women and adult males in BRICS economies for 1990–2016 thru causality and cointegration tests. The effects of the causality checks disclose that academic attainment and monetary globalization have a good sized impact on obesity in each grownup girls and men in the short run. Furthermore, cointegration analysis shows a terrible eect of educational attainment on weight problems in all BRICS economies in the long run, but the have an impact on of economic globalization on weight problems diers among the BRICS economies. Furthermore, the bad impact of instructional attainment on obesity is revealed to be relatively. higher in females than males.